Triggering a positive research and policy feedback cycle to support a transition to agroecology and sustainable food systems. Issue 7 (9th August 2017) - Miles, Albie; DeLonge, Marcia S.; Carlisle, Liz
ABSTRACT: An ecologically sustainable and socially equitable food system, one that restores ecosystem services, enhances human welfare, and promotes community-based economic development, is urgently needed. Applied agroecological research and the development of regional and community food systems are key means through which pressing ecological and social externalities may be mitigated. However, progress in both of these areas has been limited, particularly in the USA, with constraints in each likely holding the other back. In this article, we first review and explore how public investment in agroecology research and development has been limited in the USA. We then discuss how agricultural research funds could be shifted to better support the development of more resilient and equitable food systems. Finally, we explore a broader set of structural obstacles to food system change and identify key policies that could work jointly to strengthen a positive feedback cycle of research, policy, education and practice. Such a feedback cycle could work to accelerate a transition to ecological farming and food system norms that enhance natural resources sustainability, equity and resilience.